Life experiences preceding high lethality suicide attempts in adolescents at a level I regional trauma center. Issue 5 (5th March 2021) - Lyons, Vivian H.; DeCou, Christopher R.; Niehoff, Elizabeth; Moore, Megan; Rivara, Frederick P.; Rowhani‐Rahbar, Ali
Abstract: Objective: To describe life experiences associated with patterns of medically treated and documented self‐directed violence among youth who attempted suicide using highly lethal means to understand precipitating factors among youth using such lethal means. Method: Using data from a regional, level 1 Trauma center, we identified all youth suicide attempt survivors who received treatment from 2010 to 2018 for a suicide attempt with a firearm, hanging, or jump from height injury ( n = 42). We described differences in patient demographics and life experiences associated with patterns of self‐directed violence by suicide attempt mechanism. We additionally assessed mechanisms used in any prior suicide attempts to identify potential increasing lethality of mechanism selection. Results: There were 42 eligible patients included, of whom 40.5% attempted suicide with a firearm, 26.2% with hanging, 33.3% with jumping injury. A greater proportion of patients with firearm injuries endorsed social support and had fewer preparatory acts, history of self‐harming behavior, prior suicide behaviors, and fewer prior attempts compared to patients who attempted suicide with other mechanisms. Conclusions: Given our findings, means safety should remain a key strategy to prevent highly lethal suicidal behavior among adolescents, especially with firearms, given that such attempts may occur prior to formal contact with mental health services.